Morocco's Current Approach in Attaining International Recognition Over the Western Sahara (2020-2023) - Damaiyanti, Adrianita Putri; Sani, Muhammad Dzaky Putra; Ersani, Yunita Citra; Satria, Randhi (POLITEA, 2024)
Abstract Western Sahara has been a contested area between Morocco and a liberation movement called the Polisario Front for decades. Post 2020, there are growing numbers of countries who recognize, and are in favor of Moroccan efforts to maintain sovereignty, in addition to territorial integrity over the Western Sahara. Morocco continues to strengthen its Autonomy Plan by taking several approaches so that external legitimacy can be achieved. This paper aims to analyze the current efforts of the Moroccan government; that is their approach to attain international recognition for external legitimacy and territorial integrity over the Western Sahara. The research method is Qualitative-Descriptive, with data gathering technique being Library Research. Analysis in this paper is based on the Diplomacy and National Interest theories. The result indicates that the current approach of the Moroccan government is getting assertive: tit-for-tat normalization of relations, leverage politics with foreign countries, and expanding tangible presence in the Western Sahara through diplomatic building establishments, as well as setting up international cooperations. These efforts indicate the growing urgency of the Western Sahara for Morocco, and also its non-wavering resolve to protect territorial integrity.